Influencia de la iluminación de copa y clase de bosque sobre el crecimiento de las especies forestales del varillal seco, 2020 - Liao Hernández, Greyssi (2021)
To determine the influence of canopy lighting and forest class on the growth of dry tall varillal forest species, three permanent plots of one hectare each were evaluated, divided into 100 sub plots of 10 x 10 m. The growth is not normally distributed and the variances are not homogeneous. The mean annual increase in the DBH of the trees was 0.56 cm / year and it increases progressively as the diameter of the tree increases. The IMA in the trees with emergent crowns was 0.63 cm / year for the DBH; 0.0034 m2 / year for the basal area and 0.0516 m3 / year for the volume. In the trees with shaded crowns the IMA of the DBH was 0.425 cm / year, for the basal area 0.0013 m2 / ha and for the volume 0.0073 m3 / year. The presence of large trees in the subplot affected the IMA of the trees (p <0.05), the growth in DBH of the forest with trees with DBH?40cm was 0.72 cm / year, in the forest with trees with DBH between 30 and 39.99 cm it was 0.51 cm / year and in the forest under construction 0.34 cm / year; similar occurred for the basal area and volume.